2024
DOI: 10.1002/aenm.202304291
|View full text |Cite
|
Sign up to set email alerts
|

NaNbO3‐Based Multilayer Ceramic Capacitors with Ultrahigh Energy Storage Performance

Zhongqian Lv,
Teng Lu,
Zhen Liu
et al.

Abstract: With the gradual promotion of new energy technologies, there is a growing demand for capacitors with high energy storage density, high operating temperature, high operating voltage, and good temperature stability. In recent years, researchers have been devoted to improving the energy storage properties of lead‐based, titanium‐based, and iron‐based multilayer ceramic capacitors (MLCCs). However, limited research has been conducted into MLCC development using NaNbO3 (NN)‐based materials. In this paper, the succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 81 publications
(117 reference statements)
1
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first time that bulk dielectric ceramics have achieved W rec greater than 20 J cm –3 . This is also comparable to the state-of-the-art multilayer ceramic capacitors (MLCCs), ,, such as the grain orientation engineered MLCC with W rec of 21.3 J cm –3 and η of 80% . It is worth mentioning that there is still no signal of polarization saturation at E B , indicating that this material has great potential to achieve even higher performance when used as MLCCs with a small thickness of approximately 20 μm.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first time that bulk dielectric ceramics have achieved W rec greater than 20 J cm –3 . This is also comparable to the state-of-the-art multilayer ceramic capacitors (MLCCs), ,, such as the grain orientation engineered MLCC with W rec of 21.3 J cm –3 and η of 80% . It is worth mentioning that there is still no signal of polarization saturation at E B , indicating that this material has great potential to achieve even higher performance when used as MLCCs with a small thickness of approximately 20 μm.…”
Section: Resultssupporting
confidence: 59%
“…Dielectric capacitors store electrical energy as an electrostatic field, offering the highest power density of up to 10 8 MW kg –1 versus 10 2 W kg –1 for batteries and 10 5 W kg –1 for electrochemical capacitors due to their fastest charge–discharge rates at the microsecond scale. Electrostatic energy-storage ceramic capacitors represent the core components in modern pulsed power systems and are utilized in a wide variety of applications, including electric vehicles, electronic gadgets, and power grids. , As technology continues to advance, there is an increasing need to develop next-generation dielectric ceramic capacitors to meet the demands of cutting-edge applications. These capacitors are anticipated to have a high energy-storage density ( W rec ) to support miniaturization and integration, as well as high energy-storage efficiency (η) to minimize energy loss and ensure reliability. Hence, a vast range of Pb-free perovskite-structured dielectric ceramics, including BaTiO 3 (BT)-, , (Bi 0.5 Na 0.5 )­TiO 3 (BNT)-, (Bi 0.5 K 0.5 )­TiO 3 (BKT)-, NaNbO 3 (NN)-, and AgNbO 3 (AN)- based systems have been explored for electrostatic energy storage, with W rec values advancing to reach typically around 10 J cm –3 at η above 80%. Despite these substantial advances, there is an ongoing challenge to boost W rec while maintaining a high η, given the trade-off relationship between these two merits.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 12a-c present a comparison of E , J , and η values for Recent research has demonstrated that MLCC, which is constructed from a ceramic film with a layered structure [132], exhibits exceptional energy storage performance. This device is characterised by an ultrahigh J rec and superior efficiency, in addition to exhibiting outstanding temperature stability and fatigue resistance [124].…”
Section: Microstructure Modificationmentioning
confidence: 99%
“…For MLCCs, reducing the dielectric layer thickness to 5.5 µm with NN-BNT-15BMH composition achieves an E test−max of 1100 kV/cm, nearly doubling the value observed in bulk ceramics. Furthermore, NN-BNT-15BMH MLCCs demonstrate an approximate 79.9% increase in J rec compared to their ceramic counterparts [124]. Additionally, NaNbO has been explored for its utility in energy storage materials when integrated into polymer matrices to form ceramic-polymer composites.…”
Section: Microstructure Modificationmentioning
confidence: 99%
“…As a result, numerous studies have been devoted to the development of high-performance dielectrics for energy-storage applications in recent years, among which relaxor ferroelectric (FE) materials are considered as a promising candidate owing to the fast response of polar nanodomains/regions to an external electric field. 5–8…”
Section: Introductionmentioning
confidence: 99%